Examen critique de quelques hypothèses sous-jacentes à la nouvelle politique commerciale suggérée par le Conseil économique du Canada - Nappi, Carmine (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractThis paper criticizes some optimistic hypotheses implied by the Economic Council in proposing its new commercial policy for Canada.More specifically, it shows why the Samuelsonian free trade model has been misused by the Council and that its reasons for explaining the weak comparative productivity of the Canadian secondary sector are clearly insufficient. Also, the Council underestimates the total costs of the proposed policy and its regional effects.The paper suggests that the Council's recommendation would be more politically acceptable if it could demonstrate that the new policy will not continue to benefit only the Ontarian peninsula. It would also help if the Council could name the industries able in the medium term to absorb the factors displaced by the tariff elimination, and if it could refute the proposition that more free trade sectorial tests are needed before adopting the proposed very general commercial policy.